Teaching in a COVID-19 pandemic: perceptions and practices of university faculty in Spain - Lucía Sánchez-Tarazaga; Aida Sanahuja; Carla Colomer; Reina Ferrández-Berrueco (Universidad de Deusto, 2023)
The full impact of the COVID-19 crisis on higher education remains unclear, with some topics still under-researched. This research explores the challenges faced by Spanish academics during emergency remote teaching and is a pioneering study in this context due to the number of participating universities and variety of profiles of university faculty. Three focus groups were conducted to gain a deeper understanding on two dimensions: academic (methodology, materials, assessment, workload and institutional response) and personal (socio-emotional dimension, work-life balance and learnings). The main findings revealed the extensive adaptation of university faculty to the new situation and collected a series of teaching strategies. The conclusions reflect on the role that universities should play in the coming years, not only in the Spanish context but also at an international level. Most importantly, our findings can be taken into consideration for further research and teacher education policy in higher education. Received: 15 March 2022  Accepted: 24 July 2023